2007
DOI: 10.1088/0268-1242/23/1/015013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electroluminescence in p–i–n structures with nano-crystalline Si/SiO2multilayers

Abstract: Nano-crystalline Si/SiO 2 multilayers were prepared by alternately changing the ultra-thin amorphous Si film deposition and the in situ plasma oxidation process followed by the post-annealing treatments. Well-defined periodic structures can be achieved with 2.5 nm thick SiO 2 sublayers. It is shown that the size of formed nano-crystalline Si is about 3 nm. Room temperature electroluminescence can be observed and the spectrum contains two luminescence bands located at 650 nm and 520 nm. In order to improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…An intense electro-luminescence (EL) is observed by using the ITO top electrode. The broad peak centered at around 550 nm can be attributed to the recombination of carriers in nc-Si embedded in the SSM structures [19]. With increasing the applied voltage, the intensity increases gradually and the luminescence can be clearly observed visually in the dark room.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An intense electro-luminescence (EL) is observed by using the ITO top electrode. The broad peak centered at around 550 nm can be attributed to the recombination of carriers in nc-Si embedded in the SSM structures [19]. With increasing the applied voltage, the intensity increases gradually and the luminescence can be clearly observed visually in the dark room.…”
Section: Discussionmentioning
confidence: 97%
“…The detailed information on the multilayered structures preparation can be found elsewhere [19]. The 90 nm ITO is deposited onto the SSM sample by using a shadow mask with the diameter of 1.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Electroluminescence (EL) devices were fabricated by using a metal/(Si QDs/SiC) MLs/p-Si structure. The size-dependent EL characteristics were observed, which suggested that the origin of luminescence in Si QDs/SiC multilayers (MLs) can be attributed to the quantum confinement effect, which is different from that in Si QDs/SiO 2 MLs, in which the interface states played an important role in the recombination process [12], [14]. However, the emission intensity at the present stage is still low, and the output light power is on the order of several picowatts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the emission intensity at the present stage is still low, and the output light power is on the order of several picowatts. In order to further improve the emission efficiency, one of the possible ways is to utilize the p-n or the p-i-n junction structure to promote the carrier injection and recombination probability [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the matrix material surrounding the nanocrystals is usually an insulator such as oxide, investigations of the electrical properties and electroluminescence (EL) of Si-ncs are more challenging. Many researchers have investigated electrical excitation of nanocrystals for both silicon-rich materials [11][12][13][14][15][16] and superlattices [17][18][19][20][21]. Specifically, they have studied current conduction mechanisms [12][13][14]16,21] and electroluminescence behavior [11][12][13][15][16][17][18][19][20][21] material system; however, especially in the case of a superlatticebased material, further research is needed to achieve a better understanding of the electrical excitation phenomena.…”
Section: Introductionmentioning
confidence: 99%